What influences talent retention among Millennials and Generation Z? : A case study of young professionals in a multinational company - Wegelius, Henry (My University, 2025)
Shortages in available talent have prompted organisations globally to focus on talent management, which includes acquiring, selecting, developing, and retaining talent. Despite the increasing emphasis on talent management, the field of talent retention has received less attention. In particular, research concerning the retention of younger generations, especially Generation Z, remains limited. Understanding what contributes to the retention of younger employees is essential for ensuring long-term organisational competitiveness. This study examines talent retention among young professionals by utilizing Social Exchange Theory (SET) and Generational Cohort Theory (GCT). SET proposes that when employees receive valued resources from their organisation, referred to as organisational offerings in this study, they are likely to reciprocate with positive behaviours, such as commitment and continued employment. These offerings may be categorized as social or economic depending on their nature. GCT provides a framework for considering generational differences, positing that individuals born during the same period and shaped by similar events develop shared characteristics. The objective of this study is to identify which organisational offerings are most valued by young professionals, defined as individuals under the age of 35, and how these offerings influence their decision to remain with an employer. A qualitative case study approach has been adopted, utilizing an abductive strategy to collect and examine data. Semi-structured interviews were conducted with young professionals from a Finnish subsidiary of a multinational company (MNC). The study explores which types of offerings are perceived as most important in the context of retention, whether there is a collective preference for social or economic offerings, and how well the current organisational offerings meet the needs of employees. The findings indicate that certain types of offerings, particularly those related to flexibility, workplace atmosphere, and professional development, are highly valued by young professionals when considering whether to stay with an organisation. No clear preference emerged for either social or economic offerings, suggesting a balanced importance across categories. The overall perception of how well the current offerings meet employee needs was generally positive. These results highlight the complexity of retention and suggest that multiple factors contribute to a young professional’s decision to stay.

Osaavan työvoiman puute on saanut organisaatiot maailmanlaajuisesti keskittymään osaajien johtamiseen (talent management), joka kattaa osaajien hankinnan, valinnan, kehittämisen ja sitouttamisen. Vaikka osaajien johtaminen on saanut yhä enemmän huomiota, osaajien sitouttamista (talent retention) on tutkittu vähemmän. Erityisesti nuorempien sukupolvien, kuten Z-sukupolven, sitouttamiseen keskittyvä tutkimus on vähäistä. Nuorten työntekijöiden sitouttamiseen vaikuttavien tekijöiden ymmärtäminen on tärkeää organisaatioiden pitkän aikavälin kilpailukyvyn takaamisen kannalta. Tässä tutkimuksessa tarkastellaan nuorten ammattilaisten sitouttamista organisaatioon hyödyntämällä sosiaalisen vaihdon teoriaa (SET) sekä sukupolviteoriaa (GCT). SET:n mukaan työntekijät, jotka saavat organisaatioltaan arvokkaita resursseja, tässä tutkimuksessa nimetty organisaation tarjoamiksi (organisational offerings), vastaavat resursseihin myönteisellä käytöksellä organisaatiota kohtaan, mikä voi ilmetä esimerkiksi sitoutumisella organisaatioon. Tarjoamat voidaan luokitella sosiaalisiksi tai taloudellisiksi niiden luonteen mukaan. GCT tarjoaa viitekehyksen sukupolvien välisten erojen tarkasteluun ja olettaa, että samoihin aikoihin syntyneet sekä samankaltaiset tapahtumat kokeneet yksilöt omaavat yhteisiä piirteitä. Tutkimuksen tavoitteena on selvittää, mitkä organisaation tarjoamat nuoret ammattilaiset kokevat arvokkaimmiksi ja miten nämä vaikuttavat heidän päätökseensä pysyä organisaatiossa. Nuorilla ammattilaisilla viitataan alle 35-vuotiaisiin työntekijöihin. Tutkimus on toteutettu laadullisena case-tutkimuksena, jossa on hyödynnetty abduktiivista lähestymistapaa aineiston keruussa ja analysoinnissa. Puolistrukturoidut haastattelut toteutettiin monikansallisen yrityksen (MNC) suomalaisessa tytäryhtiössä työskentelevien nuorten ammattilaisten kanssa. Tutkimuksessa selvitettiin, millaiset tarjoamat koetaan merkityksellisimmiksi sitoutumisen kannalta, onko ryhmällä taipumusta enemmän sosiaalisiin tai taloudellisiin tarjoamiin, ja kuinka hyvin nykyiset tarjoamat vastaavat työntekijöiden tarpeisiin. Tulokset osoittavat, että tietyt tarjoamat, jotka liittyvät erityisesti joustavuuteen, työilmapiirin ja ammatilliseen kehittymiseen, ovat nuorten ammattilaisten näkökulmasta merkittäviä tekijöitä työpaikassa pysymisen kannalta. Selvää taipumusta sosiaalisiin tai taloudellisiin tarjoamiin ei havaittu, mikä viittaa näiden kategorioiden tasapainoiseen merkitykseen. Kokonaiskuva organisaation nykyisistä tarjoamista oli yleisesti positiivinen. Tulokset korostavat sitoutumisen moniulotteisuutta ja viittaavat siihen, että useat tekijät vaikuttavat nuoren ammattilaisen päätökseen pysyä organisaatiossa.
Keywords: human resource management; committing oneself; talent; generation Y; generation z; work satisfaction; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business